Oil price, oil price implied volatility (OVX) and illiquidity premiums in the US: (a)symmetry and the impact of macroeconomic factors - Mohammad Sharik Essa; Evangelos Giouvris (Journal of Risk and Financial Management, 2020)
We examine the impact of oil price and oil price volatility on US illiquidity premiums (return on illiquid-minus-liquid stocks), using the US Oil Fund options implied volatility OVX index. We use daily data from 2007 to 2018, taking into account the structural break in June 2009 and controlling for macroeconomic factors. Both OLS and VAR models indicate that oil price has a significantly positive impact and OVX has a significantly negative impact on premiums, for the full sample and post-crisis period. These relationships are potentially driven by investor sentiments and market liquidity. Oil price has a negative impact on premiums during the crisis period. Using an autoregressive distribution lag model and an error correction model, we analyse long- and short-run elasticities. We find that oil price has a significantly positive impact on premiums both in the long- and short-run, for the full sample and post-crisis period. OVX only has a significantly negative impact in the short-run for the full sample. The reverting mechanism to establish long-run equilibrium is effective for the full sample and post-crisis period. Illiquidity premiums do not show any asymmetric responses to oil price changes but we do find evidence of asymmetric response to OVX changes.
Keywords: E3; E44; G10; Q40; 330; autoregressive distribution lag (ARDL) model; error correction model (ECM); illiquidity premiums; macroeconomic factors; oil price; OVX; US markets